Innovative Research on Teaching Method of Taekwondo in College Elective Courses under the Background of Big Data - Yahui Chang; Su Meng; Hong Chao (Applied Bionics and Biomechanics)
In the new stage of the new century, a new technological revolution is coming quietly. This revolution is represented by “data.” The application of “big data (B D A)” technology is causing changes in all walks of life, and the use of “B D A research methods” in the education field will inevitably become a trend. The purpose of this article is an innovative research on the teaching methods of Taekwondo based on the background of B D A in a college elective course. This paper first introduces the core technology of the database by summarizing the basic theory of the database. Based on the current situation of elective Taekwondo teaching in contemporary universities, analyze the current problems and deficiencies and conduct innovative research on college elective Taekwondo teaching methods combined with Beidou technology. This paper systematically expounds the practical connection, method innovation, and implementation path between BDA technology and college elective Taekwondo teaching methods and compares the traditional Taekwondo teaching methods based on BDA technology. Experimental research shows that compared with traditional Taekwondo teaching methods, the performance of university Taekwondo teaching based on data mining (D M I) in the context of B D A is more than 20% higher, which fully reflects its feasibility and the innovation of traditional Taekwondo teaching methods needs to be solved urgently.